Questions on the logic of the argumentation (2009)
In the field of argumentation theories it is often said that logic does not have the necessary elements to logically base the most relevant arguments that are made within the framework of legal, political, psychological, humanistic and even scientific theories . If the term "logical" refers to classical logic, the author agrees. However, if the contributions of non-classical logic families are taken into account, the author does not believe it is relevant to categorically affirm such an issue. It is possible to understand why the question that guides this research is: for a certain theory that has some pretense of objectivity, is it possible to find or build a “logic system” that has the elements and the structure necessary to model the structure of its underlying logic?